Hypophosphataemic Rickets Secondary to Raine Syndrome: A Review of the Literature and Case Reports of Three Paediatric Patients’ Dental Management - Lorna Hirst; Gehan Abou-Ameira; Simon Critchlow (Case Reports in Pediatrics, 2021)
Raine Syndrome (RS) also referred to as lethal osteosclerotic bone dysplasia describes an exceptionally rare autosomal recessive disorder with an estimated prevalence of <1 in 1,000,000. Endocrinological manifestations such as hypophosphataemic rickets depict a recent finding within the phenotypic spectrum of nonlethal RS. The dental sequelae of hypophosphataemic rickets are significant. Spontaneous recurrent abscesses on noncarious teeth result in significant odontogenic pain and multiple dental interventions. The dental presentations of nonlethal RS are less widely described within the literature. Amelogenesis Imperfecta (AI), however, was recently postulated as a key characteristic. This article presents the dental manifestations and extensive restorative and oral surgical intervention of three siblings with hypophosphataemic rickets secondary to Raine Syndrome treated at Great Ormond Street Hospital for Children, a tertiary referral hospital.